Working with farmers in Ethiopia to tap the potential of Durum wheat genetic diversity to adapt to climate change - Fadda, Carlo; Bioversity International (2013)
Poster summarizing some of the activities and achievements of the Seeds for Needs Initiative in Ethiopia in honour of community seed bank opening